Defining the Future: The Role of Blockchain Technology in Monitoring International Aid Funds - Lumastari Ajeng Wijayanti; Avid Leonardo Sari; Mutia Pamikatsih; Tuti Dharmawati; Bagus Setya Rintyarna (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This article presents an in-depth analysis of blockchain technology's role in international aid fund management. The authors outline a conceptual framework illustrating how blockchain can be applied to improve aid monitoring systems, focusing on critical aspects such as transparency, recipient identification, and automation of fund distribution. We also discuss the ethical, security, and technology readiness challenges that may be faced in blockchain implementation. This article provides in-depth insight into how blockchain technology can address existing problems in international aid fund management by detailing concrete case studies and describing the research methods used. Research findings show that blockchain implementation has succeeded in increasing transparency, speeding up the distribution process, and optimising the use of aid funds. The article's result underscores the importance of continuing to pay attention to ethical, security, and inclusivity considerations while developing and implementing these technologies. By taking a holistic approach, using blockchain to monitor international aid funds can bring about significant positive change, increase efficiency, and support global development goals.